Are beekeepers conservation-friendly? A study on attitudes and values toward animals among small-scale farmers - Amâncio de Carvalho, Roberta Monique; Gomes Arandas, Janaina Kelli; Feitosa Martins, Celso; da Nóbrega Alves, Romulo Romeu; Chaves Alves, Angelo Giuseppe (Ethnobiology and Conservation, 2024)
Affective and aesthetic values attributed to nature are primary motivations that can influence human attitudes toward and economic valuation of biodiversity. The expression of these values, however, depends on direct contact and positive experiences with nature. In this sense, research on activities that favor beneficial human-nature interactions, such as beekeeping, can contribute to understanding the factors (including affective and aesthetic) that influence attitudes toward and economic valuation of biodiversity. Our research was carried out at Sítio Xixá, a rural locality originally covered by Atlantic Forest in the state of Pernambuco, Brazil. We investigated attitudes toward a variety of locally known animals and their economic value among two groups of small-scale farmers: keepers and nonkeepers of stingless bees. We assumed that keepers of stingless bees would cite more affective-aesthetic attitudes toward animals and would be more willing to pay for animal conservation than nonbeekeepers. The data were collected via semistructured interviews. Beekeepers cited more affective-aesthetic attitudes than nonbeekeepers did. On the other hand, beekeepers were less willing to pay for animal conservation than nonbeekeepers were. It seems that the expression of affective-aesthetic values directed toward animals tends to occur more frequently in groups of people who maintain activities that favor beneficial interactions with the environment, such as beekeepers. However, these values reflect nonmaterial aspects that people attribute to nature and may not be economically valued by human groups. Therefore, nonmaterial values that human populations attribute to nature, such as those related to affection and aesthetics, should be considered in conservation proposals involving the public.